Dimensions Of Entrepreneurial Competence Of The Rural Entrepreneurs Of Mudra Yojana With The Help Of Conceptual Model (Journal of Namibian Studies : History Politics Culture, 2023)
India is an example of a developing nation with an adequate supply of natural resources and human capital but a need for greater capital resources. Its population is over 140.76 million. Most people in India live below the poverty line and live in the rural and interior parts of the country. They were depressed of the benefits of the formal banking system. They belong to scheduled castes, tribes, and other backward classes. It is to be noted that most of the micro-enterprises, retail, or trading activity are initiated or controlled by them, with no exposure to  financial literacy, financial  accessibility education, formal training. The biggest problem these small businesses adaptability to cope with the challenges posed by the dynamic business environment. They need to learn about the scheme given by our government. This paper mainly studies the influence of the level of entrepreneurial competence of the rural entrepreneurs of the Telangana region. The Conceptual Model constructs are financial empowerment, entrepreneurial competence, entrepreneurial problems, business performance, and socioeconomic empowerment.Design/methodology/approach: The paper is based on qualitative research and suggests a theoretical model explaining with the idea of entrepreneurial problems, business performance, and socioeconomic empowerment. The Mudra Yojana is a significant initiative by the Government of India aimed at providing financial support to rural entrepreneurs. Entrepreneurial competence refers to the skills, abilities, and attributes possessed by individuals to effectively start, manage, and grow a business. For rural entrepreneurs under the Mudra Yojana, several dimensions of entrepreneurial competence can be identifiedFindings: The paper develops a Conceptual Model grow a business. They need to counter to variations in market trends, consumer preferences, and technological advancements the limited resources in rural areas. Entrepreneurs must showcase resourcefulness in utilizing available assets optimally. This includes Stocking system properly local talent, raw materials, and infrastructure to their advantage. They can predict future lossesResearch limitations/implications: The paper is based on entrepreneurial competence to do the business analysis to get the true pictures which will help them to make truthful and accurate decisions.